2012
DOI: 10.1039/c1ob06516e
|View full text |Cite
|
Sign up to set email alerts
|

Ruthenium-catalysed oxidative synthesis of heterocycles from alcohols

Abstract: Ruthenium-catalysed hydrogen transfer has been successfully used for the conversion of alcohols into either 2,3-dihydroquinazolines or quinazolines. The choice of reaction conditions allows for the selective formation of either heterocycle and the methodology can also be applied to the sulfonamide analogue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
36
0
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 140 publications
(37 citation statements)
references
References 53 publications
0
36
0
1
Order By: Relevance
“…A broad range of medicinal properties are reported for quinazolinones, such as anticancer [23][24][25][26][27], antibacterial [28][29][30], antifungal [31][32][33][34][35], antimalarial [36], antiviral [37,38] as well as anti-microbial cholinesterase inhibitors [39,40], making quinazolinone a privileged class of N-containing heterocyclic scaffolds ( Figure 1). Due to diverse biological applications in pharmaceutical industry numerous synthetic methodologies were developed for the synthesis of quinazolinones [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. These methods furnish the quinazolinones through reactions of readily available anthranilamide (2-aminobenzamide) with aldehydes, alcohols, esters, carboxylic acids, methyl arenes and amines under harsh reaction conditions in the presence of transition metals, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A broad range of medicinal properties are reported for quinazolinones, such as anticancer [23][24][25][26][27], antibacterial [28][29][30], antifungal [31][32][33][34][35], antimalarial [36], antiviral [37,38] as well as anti-microbial cholinesterase inhibitors [39,40], making quinazolinone a privileged class of N-containing heterocyclic scaffolds ( Figure 1). Due to diverse biological applications in pharmaceutical industry numerous synthetic methodologies were developed for the synthesis of quinazolinones [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. These methods furnish the quinazolinones through reactions of readily available anthranilamide (2-aminobenzamide) with aldehydes, alcohols, esters, carboxylic acids, methyl arenes and amines under harsh reaction conditions in the presence of transition metals, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These methods furnish the quinazolinones through reactions of readily available anthranilamide (2-aminobenzamide) with aldehydes, alcohols, esters, carboxylic acids, methyl arenes and amines under harsh reaction conditions in the presence of transition metals, etc. [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. Despite a high number of synthetic methodologies in literature, there is not much known for the synthesis of quinazolinones via Due to diverse biological applications in pharmaceutical industry numerous synthetic methodologies were developed for the synthesis of quinazolinones [41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57][58].…”
Section: Introductionmentioning
confidence: 99%
“…In this context, several synthetic methods have been developed to synthesize benzothiadiazine 1,1-dioxides and their analogues. The condensations of 2-aminobenzenesulfonamides with urea, isocyanates, carboxylic acid derivatives or other carbonyl reagents are the most used methods [1215]. These reactions were usually carried out under harsh reaction conditions, causing the formation of byproducts.…”
Section: Introductionmentioning
confidence: 99%
“…We found that each set of nucleophiles required a minor variation in the conditions to optimize the yields. The supplementary nucleophiles which can be added to the methylenation reaction are diverse, including nitro compounds (14,15), ketones (16,17) and even tert-butyl hydroperoxide to form epoxides (18,19) in good to excellent yields, and all in one pot from methylene ketones. In addition, we were also able to perform a tandem rhodium-catalyzed conjugate addition of a boroxine or boronic acid to form the doubly benzylated compound 20, and analogue 21, again in good overall yields for a sequence which involves multiple reaction steps.…”
mentioning
confidence: 99%
“…In addition, we examined the oxidative (and aromatizing) transformation of the three 1,5-diketone derivatives made in this work (Scheme 5). [14] Reaction of the compounds 5, 16, and 17 with either ammonium acetate and Cu II or hydroxylamine hydrochloride formed the corresponding tetrasubstituted pyridines in excellent yields.…”
mentioning
confidence: 99%